Office Automation: A Review of the Litterature - Hugues, Karen (Relations industrielles / Industrial Relations, 1989)
The impact of new technologies on clerical workers has been intensely debated. This paper assesses current research on the key issues of employment, skill and quality of working life, drawing implications for Canadian clérical workers. The author argues that a reliance on deterministic research models has produced unduly pessimistic forecasts about the impact of new office technologies. Research which is sensitive to the mediated nature of automation is necessary for improving forecasts for the Canadian office. So too is the consideration of employer, union and state activity in influencing automation outcomes.